THE INFLUENCE OF POLITICAL DYNASTY ON THE DEMOCRACY CLIMATE: PENGARUH DINASTI POLITIK TERHADAP IKLIM DEMOKRASI - Adhe Ismail Ananda (Constitutional Law Society, 2023)
Indonesia's political culture does have its own characteristics, where regions with a variety of local cultural values also always give different political nuances. However, if we pay close attention, almost no region is free from the legacy of feudalism values, patrimonial practices, patronage and the characteristics of a communal society which tend to be very permissive. This condition then gave birth to political dynasties, one thing that is also a problem for democracy in our country. This research is a doctrinal research or normative legal research. Political dynasties are primitive reproductive systems of power because they rely on the blood and lineage of only a few people. Political dynasty can also be interpreted as a strategy to maintain power in order to remain in the family circle. Political dynasties tend to give rise to multiplication of actors (actors that appear only within dynasties), not pluralism of actors (actors that appear tend to vary from various backgrounds). The presence of political dynasties that encompasses power struggles at regional to national levels makes it difficult to realize the substance of democracy itself. The growth of political dynasties, especially in the regions, cannot be separated from the role of political parties and regulations regarding regional elections. The oligarchy within political parties causes the candidacy and nomination mechanisms to not work as they should. So far, there has been a tendency for political parties to nominate candidates based on the wishes of party elites, not through democratic mechanisms that take into account the abilities and integrity of the candidates.